(untitled) (Ágora de Heterodoxias, 2017)
The following article presents the main reasons that led the United Nations to develop the agreement signed in the year 2015 to counteract the global warming since the implementation of the 2030 Agenda for Sustainable Development. Costa Rica is among the signing countries which in order to achieve with the proposed plan, developed an index of social progress that measures the social, human and environment progress in all the communities, in order to be a country with a sustainable development by the year 2030. Knowing the objectives that constitute the 2030 Agenda for Sustainable Development is identified the level of implementation that Costa Rica is doing. Applying a qualitative methodology and making a literature review of the thematic related, to compile the advances the country has. The main results show that Costa Rica’s Government, in the environment subject, has created new laws to minimize the environmental damage. It worries the high gaps in different parts of the country, where cities of the central zone have high indexes of social progress, while some cities near the border to Nicaragua, Panama and the Pacific and Atlantic coasts have very low results. Knowing those gaps will permit to improve the action plans to follow by Costa Rica, and opens the way to new investigations about how to make more equitable the resources available for all its inhabitants, one of the main objectives of the sustainable development.